A prospective cross-sectional study of prevalence of sensorineural hearing loss in patients with chronic otitis media - Mili, Mohan K.; Payeng, Rijumoni; Jayan, Laya K.; Nath, Bijit K.; Patel, Prakash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Chronic otitis media (COM) accounts for one of the major causes of acquired hearing loss, especially in developing countries. The hearing loss is mostly conductive, but many cases show mixed hearing loss of varying degrees, suggesting involvement of the sensorineural component as well. This study aims to estimate the prevalence of sensorineural hearing loss (SNHL) in patients of chronic otitis media and assess the clinical factors playing a role in sensorineural hearing. Methods: Prospective analysis of clinical and surgical data of 80 patients with COM was studied. The bone conduction thresholds measured in both normal and affected ears were compiled. Disease duration, presence of cholesteatoma and its association with degree of SNHL were evaluated. Results: In this study, COM was more common in the younger age group with a female preponderance. Prevalence of SNHL in COM was found to be 31%, out of which 21% had squamosal and 10% had mucosal disease. Mean bone conduction thresholds were significantly higher in the affected ear compared to the normal ear (p<0.05). No significant difference was found concerning the duration of disease. Although the incidence of sensorineural hearing loss was more in patients with squamosal disease, the degree of hearing loss did not vary with the presence or absence of cholesteatoma. Conclusions: COM can lead to significant sensorineural hearing loss, and prompt evaluation for better management and hearing outcomes.